In Silico Discovery of Plant-Origin Natural Product Inhibitors of Tumor Necrosis Factor (TNF) and Receptor Activator of NF-κB Ligand (RANKL) - Melagraki, Georgia; Ntougkos, Evangelos; Papadopoulou, Dimitra; Rinotas, Vagelis; Leonis, Georgios; Douni, Eleni; Afantitis, Antreas; Kollias, George (Frontiers in Pharmacology, 2018)
An in silico drug discovery pipeline for the virtual screening of plant-origin natural products was developed to explore new direct inhibitors of TNF and its close relative RANKL, both representing attractive therapeutic targets for many chronic inflammatory conditions. Currently, direct TNF inhibition through identification of potent small molecules is a highly desired goal, however, it is often hampered by severe limitations. Our approach yielded a priority list of 15 natural products as potential direct TNF inhibitors that were subsequently tested in vitro against TNF and RANKL. We thus identified two potent direct inhibitors of TNF function with low micromolar IC50 values and minimal toxicity even at high concentrations. Most importantly, one of them (A11) was proved to be a dual inhibitor of both TNF and RANKL. Extended molecular dynamics simulations with the fully automated EnalosMD suite rationalized the mode of action of the compounds at the molecular level. To our knowledge, these compounds constitute the first natural product TNF inhibitors, one of which being the first natural product small-molecule dual inhibitor of TNF and RANKL, and could serve as lead compounds for the development of novel treatments for inflammatory and autoimmune diseases.